Thermal stress analysis on non-metal pipe - Abd Hamis, Saiful Mizwan (2018)
The scope of this study is to find out the performance of non-metal pipe, namely Polyether Ether Ketone (PEEK) in high pressure and high temperature (HPHT) condition compared to normal steel pipe. The research is complete by applying thermal stress analysis. Thermal stress analysis consists of thermal and stress studies which is to investigate the temperature and stress distribution. The Fluid Structure Interaction (FLUENT) revealed that final temperature at steel pipe due to temperature distribution from internal fluid is higher than Polyether Ether Ketone which is 356.62 K compared to 301.26 K. The temperature is after pass through the material wall. Means that Polyether Ether Ketone sustain better temperature than steel. Equivalent strain and Equivalent Stress shows that Polyether Ether Ketone deals lower pressure than steel. The dimension changes after exerted by 15,000 psi pressure for steel is higher than Polyether Ether Ketone. In other words, Polyether Ether Ketone withstand low pressure compared to steel with the same input. Thus, Polyether Ether Ketone was preferable to be used in HPHT condition.to the others